Pengakuan dan Pelaksanaan Putusan Arbitrase Asing - Hikmah, Mutiara (Indonesian Journal of International Law, 2008)
Indonesia has ratified New York Convention on Recognition adn Enforcement of Foreign Arbitral Awards, 1958. This convention is sponsored by the United Nations. The ratification of that convention is proclaimed in The State Gazette 40, 1981 and President Dectee 34, 1981. Recognition and enforcement of foreign arbitral awards is also governed in Arbitration Act 1999. Yet, the court desicions seem not following the written law. It can be seen from some cases in Indonesia as explained in this article.